2022
DOI: 10.1038/s41531-022-00400-0
|View full text |Cite
|
Sign up to set email alerts
|

Druggable transcriptomic pathways revealed in Parkinson’s patient-derived midbrain neurons

Abstract: Complex genetic predispositions accelerate the chronic degeneration of midbrain substantia nigra neurons in Parkinson’s disease (PD). Deciphering the human molecular makeup of PD pathophysiology can guide the discovery of therapeutics to slow the disease progression. However, insights from human postmortem brain studies only portray the latter stages of PD, and there is a lack of data surrounding molecular events preceding the neuronal loss in patients. We address this gap by identifying the gene dysregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 139 publications
2
6
0
Order By: Relevance
“…LAMA1, LAMA3 and LAMA5, other laminins, are targets of the approved drug lanoteplase, used in the treatment of myocardial infarction but with unknown mechanisms of action 89 . In an analysis aimed at identifying potential drug candidates based on perturbed transcriptomic pathways in Parkinson’s disease, lanoteplase emerged as the candidate with strongest enrichment 90 .…”
Section: Resultsmentioning
confidence: 99%
“…LAMA1, LAMA3 and LAMA5, other laminins, are targets of the approved drug lanoteplase, used in the treatment of myocardial infarction but with unknown mechanisms of action 89 . In an analysis aimed at identifying potential drug candidates based on perturbed transcriptomic pathways in Parkinson’s disease, lanoteplase emerged as the candidate with strongest enrichment 90 .…”
Section: Resultsmentioning
confidence: 99%
“…LAMA1, LAMA3 and LAMA5, other laminins, are targets of the approved drug lanoteplase, used in the treatment of myocardial infarction but with unknown mechanisms of action 107 . In an analysis aimed at identifying potential drug candidates based on perturbed transcriptomic pathways in Parkinson’s disease, lanoteplase emerged as the candidate with strongest enrichment 108 .…”
Section: Resultsmentioning
confidence: 99%
“…Gene expression patterns shape the electrophysiological and morphological phenotypes. Patch-seq provides a multimodal analysis strategy to identify potential molecular markers or pathways that predict the phenotype of single neurons [ 161 , 162 ]. Using Patch-seq combined with Weighted Gene Co-expression Network Analyses of single human neurons in culture, certain gene clusters are correlated with neuronal maturation as determined by electrophysiological characteristics, and a list of candidate genes has been identified that have the potential to serve as biomarkers of neuronal maturation [ 163 ].…”
Section: Linking Transcriptomes With Morphological and Electrophysiol...mentioning
confidence: 99%